2011
DOI: 10.1073/pnas.1102716108
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-guided complex from a bacterial immune system enhances target recognition through seed sequence interactions

Abstract: Prokaryotes have evolved multiple versions of an RNA-guided adaptive immune system that targets foreign nucleic acids. In each case, transcripts derived from clustered regularly interspaced short palindromic repeats (CRISPRs) are thought to selectively target invading phage and plasmids in a sequence-specific process involving a variable cassette of CRISPR-associated ( cas ) genes. The CRISPR locus in Pseudomonas aeruginosa (PA14) includes four cas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
409
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 423 publications
(436 citation statements)
references
References 22 publications
26
409
1
Order By: Relevance
“…Csy1-4 proteins constitute the cascade [32], wherein Csy4 func-tions in processing crRNA transcripts, whereas Csy1-3 proteins are required to stabilize the crRNA produced by Csy4 [32]. On the other hand, Cas1 is not required for this procedure, but has a role in acquiring new spacers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Csy1-4 proteins constitute the cascade [32], wherein Csy4 func-tions in processing crRNA transcripts, whereas Csy1-3 proteins are required to stabilize the crRNA produced by Csy4 [32]. On the other hand, Cas1 is not required for this procedure, but has a role in acquiring new spacers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Both Cas9 [26,27] and Cpf1 [19,24] have been shown to have a seed sequence at the PAM-proximal side of the protospacer, which is critical for DNA recognition and cleavage. The 10-nt seed sequence of the guide RNA has been shown to form a preordered A-form conformation in the Cas9-sgRNA complex to facilitate guide-target duplex formation [14], a mechanism that has also been found in eukaryotic Argonaute complexes [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In P. aeruginosa, numerous spacers in the CRISPR loci are complementary to sequences in bacteriophage genomes [5,6]. While some of the spacers are perfectly complementary, others contain several mismatches.…”
mentioning
confidence: 99%
“…The complementary target sequence is referred to as a protospacer (i.e., origin of the spacer) and the consecutive GC base pairs are referred to as the Protospacer Adjacent Motif (PAM). Previous DNA binding studies have shown that the PAM and DNA target base-pairing with the first 8 bases of the crRNA, the so-called "seed" region, are critical for high-affinity binding [6]. Csy complex binding to a target with the correct PAM, base pairing within the seed, and sufficient base pairing throughout the remainder of the protospacer, trigger recruitment of a trans acting nucleasehelicase protein called Cas3 that degrades the target DNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation